Comparative study of elective cholecystectomy with and without antimicrobial prophylaxis: A prospective randomized study - Pokhariya BMS (Asian Journal of Medical Sciences, 2024)
Background: Cholecystectomy is one of the most common, clean, and contaminated surgery operations performed by surgeons worldwide. Antibiotic prophylaxis in elective cholecystectomy is a controversial issue and our study was undertaken to evaluate the rate of infection and the usefulness and efficacy of antibiotic prophylaxis in elective cholecystectomies. Aims and Objectives: The aims and objectives are to study antimicrobial prophylaxis on elective laparoscopic cholecystectomy and to compare surgical site infections (SSI) between the two groups after laparoscopic cholecystectomy with respect to (a) duration of surgery, (b) post-operative pain, (c) complications encountered, and (d) post-operative hospital stay. Materials and Methods: Patients were randomly divided into the study group (Group A) and the control group (Group B). Antibiotic dose of ceftriaxone + sulbactam 1.5 g will be administered intravenously 2 h before induction of anesthesia for the patients in the study Group A (n=30), and no antibiotic will be administered prophylactically to the control Group B (n=30). Results: In the study group, one patient developed fever, and in the control Group, 4 patients developed fever. In this study, SSIs were considered. In the study group, two patients (6.67%) developed pus discharge from the port site which was considered superficial infection, and in the control group, five patients (16.67%) developed pus discharge. Conclusion: Based on our study, in elective cholecystectomy, a single dose of intravenous ceftriaxone + salbactam 1.5 g given before the operative procedure does not lead to a higher SSI rate as compared to the conventionally given antibiotics which are continued postoperatively for a variable length of time.